2018
DOI: 10.1007/s11606-018-4468-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low Back Pain Risk-Stratification Strategy on Patient Outcomes and Care Processes: the MATCH Randomized Trial in Primary Care

Abstract: National Clinical Trial Number NCT02286141.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
133
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(151 citation statements)
references
References 28 publications
(38 reference statements)
4
133
1
1
Order By: Relevance
“…For example, a targeted psychologically informed management approach using the Keele STarT Back Screening Tool as a stratification measure for acute low back pain has been developed and shown to be more effective than non‐stratified primary care in the United Kingdom (Hill et al, ). Several follow‐up investigations have attempted to adapt and implement a similar approach in U.S. primary care settings (Cherkin et al, ) and outpatient physical therapy (Beneciuk & George, ). The Keele STarT Back Screening Tool is a short (nine items) and easy to administer questionnaire that is clinically feasible for determining psychosocial risk in patients with low back pain.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a targeted psychologically informed management approach using the Keele STarT Back Screening Tool as a stratification measure for acute low back pain has been developed and shown to be more effective than non‐stratified primary care in the United Kingdom (Hill et al, ). Several follow‐up investigations have attempted to adapt and implement a similar approach in U.S. primary care settings (Cherkin et al, ) and outpatient physical therapy (Beneciuk & George, ). The Keele STarT Back Screening Tool is a short (nine items) and easy to administer questionnaire that is clinically feasible for determining psychosocial risk in patients with low back pain.…”
Section: Discussionmentioning
confidence: 99%
“…The trial also found that matching treatment and referral pathways to prognostic factors led to modest improvements in disability compared with usual care. However, the result was not replicated in the second trial in the US setting 32. These conflicting results may mean that further research is required to examine the true effectiveness of stratified care across different healthcare settings and countries.…”
Section: What About Stratified Care?mentioning
confidence: 96%
“…A randomized controlled trial by Hill et al () held in the United Kingdom found that the intervention group, stratified to care based off their SBT score, had significantly improved disability scores at 4 and 12 months, improved health‐related quality of life, and decreased cost of care when compared to the control group. However, two subsequent trials in which the SBT was used for primary care risk stratification in the U.S. and Denmark did not improve patient outcomes (Cherkin et al, ; Riis et al, ).…”
Section: Multidimensional Psychosocial Screening Toolsmentioning
confidence: 99%